2008
DOI: 10.1007/s11255-007-9300-0
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium carbonate for phosphate control in patients on hemodialysis. A randomized controlled trial

Abstract: Background Magnesium salts bind dietary phosphorus, but their use in renal patients is limited due to their potential for causing side effects. The aim of this study was to evaluate the efficacy and safety of magnesium carbonate (MgCO 3 ) as a phosphatebinder in hemodialysis patients. Methods Forty-six stable hemodialysis patients were randomly allocated to receive either MgCO 3 (n = 25) or calcium carbonate (CaCO 3 ), (n = 21) for 6 months. The concentration of Mg in the dialysate bath was 0.30 mmol/l in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…An experimental study demonstrated that dietary supplementation with Mg reduced medial calcification of the grafted aorta in the rat [22]. Potential benefits have also been attributed to Mg carbonate use as an effective, less toxic and less expensive phosphate binder in HD patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…An experimental study demonstrated that dietary supplementation with Mg reduced medial calcification of the grafted aorta in the rat [22]. Potential benefits have also been attributed to Mg carbonate use as an effective, less toxic and less expensive phosphate binder in HD patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…Several past studies have suggested that hypermagnesemia, by increasing total body and bone magnesium, may lead to worsening of renal osteodystrophy [4], delayed nerve conduction [5], and pruritus [6], and that lowering plasma [Mg] can improve these abnormalities [4,5,6]. More recently, use of magnesium as an inexpensive phosphate binder [7,8,9,10,11] and the possible role of high magnesium in adynamic bone disease [12] have led to use of a lower dialysate [Mg]. Whereas mild hypermagnesemia is expected with use of a dialysate [Mg] of 1.5 mEq/l [13,14,15,16], a dialysate [Mg] of 1.0 mEq/l has generally been associated with either normal plasma [Mg] or mild hypermagnesemia [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium is known for its protective action against calcification and it is not a surprise that has a favorable effect on vascular calcification. Either alone, [16] or in combination with calcium, is an effective phosphate binder. Nevertheless, caution is needed to avoid prescribing increased doses in order to avoid calcium burden.…”
Section: Editorialmentioning
confidence: 99%